Adaptasi Salinitas Mampu Meningkatkan Pertumbuhan dan Kelulushidupan Benih Nila Sultana (Oreochromis niloticus) : (Kelas : Osteichtyes; Famili : Cichlidae) - Zuib, Mauvi Ahdha; Rejeki, Sri; Harwanto, Dicky (Jurnal Kelautan Tropis, 2024)
Sultana nile tilapia (Oreochromis niloticus) is a superior fish strains that can live in waters with high salinity (20−32‰). To improve the endurance of high salinity, it is necessary to prepare the seed as the salinity adaptation method during the fish seeds nursing stage. The purpose is to examine the effect of salinity adaptation on the growth and survival of Sultana nile tilapia during the fish seeds nursing stage. The research was conducted on January 9th−February 10th 2023 at the Brackish Water Cultivation Fisheries Center, Jepara. Fish tests were used in the experiment with an initial weight average of 3.6±0.01 g at densities of 1 fish/1.5L. Commercial feed (30% crude protein) was given thrice a day at 5% of body weight. This research used RAL with four treatments of different levels of salinity increase and three replications. There is 0‰ (as control), increment 1‰/1 day-1, increment 2‰/2days-1, and increment 3‰/3 days-1 conducted for 30 days. Water quality monitoring is done daily. The results showed that the adaption methods in salinity changes of tilapia had significantly different (p<0.05) in growth, but not significantly different (p>0.05) on survival rate and absolute length of Sultana. The best growth and survival rate are found in treatment S1 (absolute weight of 10.53±0.64 g fish-1, absolute length of 2.9±0.10 cm, SGR of 4.56±0.15%/day-1, and SR 100%.